Spin-offs from research centers at a research university - Steffensen, Morten; Rogers, Everett M.; Speakman, Kristen (Journal of Business Venturing, 2000)
Spin-offs are a means of technology transfer from a parent organization that represent a mechanism for creating jobs and new wealth. We investigated 6 of the 19 spin-offs from the 55 research centers at the University of New Mexico (UNM) in 1997. The Albuquerque area in Northern New Mexico is rich in technology, thanks to the presence of three large Federal R&D laboratories and the University of New Mexico. University administrators and community leaders envision a future technopolis (technology city), but achieving this goal will be difficult, given the lack of needed infrastructure, entrepreneurship, and venture capital in the Albuquerque region. Nevertheless, in the early 1990s the amount of research funding at UNM increased at a faster rate than at other U.S. research universities (total research funding rose to $197 million in 1996). Most of this increase (about 85%) took place through the efforts of UNM's 55 research centers, which are multidisciplinary units supported mainly by funding from federal and state government agencies, private companies, and foundations. The research centers transfer technological innovations across the university's boundary via various mechanisms, including spin-offs. A spin-off is a new company that is formed (1) by individuals who were former employees of the parent organization (a UNM research center in the present case), and (2) a core technology that is transferred from the parent organization. A previous study by the present authors identified 71 spin-offs from the three federal R&D laboratories in New Mexico. The fact that high-technology spin-offs are occurring in New Mexico, and at an increasing rate, suggests that a technopolis may be getting underway. In recent years the University of New Mexico and the federal R&D laboratories have established organizational and procedural mechanisms intended to encourage spin-offs and other types of technology transfer such as patenting and technology licensing. An important factor in the success of a spin-off company is the degree of support that it receives from its parent organization. The six UNM spin-offs of study here experienced few conflicts with their parent, in each case a university-based research center. However, lengthy negotiations with university officials over intellectual property rights to a spin-off's core technology were often involved. The director of a spin-off's parent research center usually played a key role in the spin-off process. Often the university research center continued to provide laboratory facilities and access to research equipment to the spin-off. Generally, both the spin-off and the parent organization perceived of the spin-off process as a win-win situation (which might not be the case when the parent is a private company and the spin-off becomes a competitor). In the present investigation we identify two types of spin-offs: (1) planned, when the new venture results from an organized effort by the parent organization, and (2) spontaneously occurring, when the new company is established by an entrepreneur who identifies a market opportunity and who founds the spin-off with little encouragement (and perhaps with discouragement) from the parent organization. Both types of spin-offs were represented in the present study. UNM professors, directors of the parent research centers, and others played important roles in instigating three of the six spin-offs, while the other three were launched mainly by entrepreneurs. Spin-offs represent an important mechanism for technology transfer, as a spin-off is typically founded around a core technological innovation that was initially developed at the parent organization. One reason that a research university is a vital ingredient in a technopolis is because of the considerable role that university-based research centers play in spinning-off new ventures. Stanford University in Silicon Valley, MIT on Route 128, and the University of Texas in Austin are all examples of this important relationship. The University of New Mexico is a smaller research university than Stanford, MIT, or Texas, but it is beginning to play a similar role in the spin-off process. If indeed a technopolis eventually develops in Albuquerque, perhaps in 10 or 20 years, lessons may be learned about the roles of a research university and its research centers (and federal R&D laboratories), in contributing to regional economic development.